Message Framing untuk Meningkatkan Frekuensi Menyikat Lidah - Jumra Sayman; Rohmah Rifani; Ahmad Ridfah (CV. Ulil Albab Corp, 2022)
Since the awareness of tongue cleansing for health’s sake in a real life is still considered as useless activity, several people denied to clean their tongue regularly. This research was purposely conducted to investigate the effect of message framing towards tongue cleaning behaviour. This quasi-experiment was designed for the classic experiment or two group, pre-test & post-test with follow up. The participants (N=20) involving in this study was grouped into two teams, and both the groups were instructed to read the article with gain and loss framed message. The result of Friedman test clearly indicated that there was a significant difference of the mean score of brushing tongue frequency before and after reading the article, including follow up among both of the group 1 (M=0.2; M=3) (p = 0.000; p < 0.05) and group 2 (M=1; M=4.7) (p = 0.000; p < 0.05). On the other hand, Kruskal-Wallis experiment revealed that there was a significant difference of the mean score of posttest and follow up between group 1 (M=7.50) and group 2 (M= 13.5) (p = 0.017; p < 0.05). The final result of this study showed that both of the message framing styles were effective to increase the frequency of cleaning the tongue among the participant, which the loss framed style was more effective. The message framing was effective as an intervention in promoting the health behavior.